2007
DOI: 10.1080/10428190701615900
|View full text |Cite
|
Sign up to set email alerts
|

Lack of nucleophosmin mutation in patients with myelodysplastic syndrome and acute myeloid leukemia with chromosome 5 abnormalities

Abstract: Nucleophosmin (NPM1) gene exon 12 mutations are frequently present in patients with acute myeloid leukemia (AML) with normal karyotype. The NPM1 gene is located on chromosome 5q35, which is often affected in myeloid malignancies including myelodysplastic syndrome (MDS). This suggests that the NPM1 gene is a one of the target genes affected by chromosome 5 abnormalities and play a role in the development of MDS. It has not been clarified whether MPM1 mutations are present in patients with MDS and AML with chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Our findings add to the body of evidence that the NPM1 mutation is a founder genetic lesion in NPMc + AML: i) cytoplasmic mutated nucleophosmin is specific for AML 1,30,31 and clinically shows close association with AML of de novo origin 1,[32][33][34] ; ii) all NPM1 mutations generate changes at the C-terminus of nucleophosmin protein which appear to maximise nuclear export of NPM leukemic mutants, 3,[35][36][37] pointing to cytoplasmic dislocation of the mutants as the central event for leukemogenesis; iii) NPM1 mutations are mutually exclusive with other recurrent genetic abnormalities, 1,38 with the exception of rare cases in which both NPM1 and CEPBA (or FLT3-ITD) mutations are found; 15 iv) they are stable during the course of the disease 39,40 as the same type of NPM1 mutation is consistently detected at relapse in medullary and extramedullary sites; 40 and v) quantitative real-time PCR shows that NPM1 mutations disappear at complete remission. 41,42 The major finding in the present study is that the onemutation mathematical model can explain the age specific incidence in NPMc + AML.…”
Section: Discussionmentioning
confidence: 76%
“…Our findings add to the body of evidence that the NPM1 mutation is a founder genetic lesion in NPMc + AML: i) cytoplasmic mutated nucleophosmin is specific for AML 1,30,31 and clinically shows close association with AML of de novo origin 1,[32][33][34] ; ii) all NPM1 mutations generate changes at the C-terminus of nucleophosmin protein which appear to maximise nuclear export of NPM leukemic mutants, 3,[35][36][37] pointing to cytoplasmic dislocation of the mutants as the central event for leukemogenesis; iii) NPM1 mutations are mutually exclusive with other recurrent genetic abnormalities, 1,38 with the exception of rare cases in which both NPM1 and CEPBA (or FLT3-ITD) mutations are found; 15 iv) they are stable during the course of the disease 39,40 as the same type of NPM1 mutation is consistently detected at relapse in medullary and extramedullary sites; 40 and v) quantitative real-time PCR shows that NPM1 mutations disappear at complete remission. 41,42 The major finding in the present study is that the onemutation mathematical model can explain the age specific incidence in NPMc + AML.…”
Section: Discussionmentioning
confidence: 76%
“…[5][6][7][8]10 Thus, the difference in frequency of NPM1 mutations between therapy-related and de novo AML seems to rely mainly on a difference in cytogenetic characteristics, with a normal Table 1 Nucleotide and theoretical peptide sequences of the NPM1 exon 12 translated region 4 The occurrence of NPM1 mutations in de novo MDS is uncommon and controversial. 30,31 Our observation of three cases of NPM1 mutations in patients with t-MDS is therefore surprising. All three cases, however, were atypical.…”
Section: Discussionmentioning
confidence: 92%
“…26 Although NPM1 and FLT3 mutations are two of the most common molecular abnormalities in acute myeloid leukemia, particularly within the cytogenetically normal group, they are relatively uncommon in myeloproliferative neoplasms and myelodysplastic syndromes. 14,[28][29][30] Studies that evaluated chronic myelomonocytic leukemia specifically found the NPM1 mutation in 5-13% Transformed chronic myelomonocytic leukemia of patients. 14 In one study, all three NPM1-mutated chronic myelomonocytic leukemia patients had rapid progression to overt acute myeloid leukemia, whereas in the other study, one of the two patients progressed to acute myeloid leukemia.…”
Section: Discussionmentioning
confidence: 99%